2016
DOI: 10.1007/s00787-016-0899-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic personality traits in 5 year old twins: the importance of genetic and shared environmental influences

Abstract: There is limited research on the genetic and environmental bases of psychopathic personality traits in children. In this study, psychopathic personality traits were assessed in a total of 1189 5-year-old boys and girls drawn from the Preschool Twin Study in Sweden. Psychopathic personality traits were assessed with the Child Problematic Traits Inventory, a teacher-report measure of psychopathic personality traits in children ranging from 3 to 12 years old. Univariate results showed that genetic influences acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 79 publications
0
24
1
1
Order By: Relevance
“…Indeed, recent reports have shown that CU traits can be reliably assessed during preschool (Kimonis et al, 2016) and are heritable by age 5 (Tuvblad, Fanti, Andershed, Colins & Larsson, 2016). However, our results also suggest that new, distinct genetic contributions emerge later during childhood.…”
Section: Phenotypic Results the Moderate Stability Of Individual Difcontrasting
confidence: 51%
“…Indeed, recent reports have shown that CU traits can be reliably assessed during preschool (Kimonis et al, 2016) and are heritable by age 5 (Tuvblad, Fanti, Andershed, Colins & Larsson, 2016). However, our results also suggest that new, distinct genetic contributions emerge later during childhood.…”
Section: Phenotypic Results the Moderate Stability Of Individual Difcontrasting
confidence: 51%
“…The youngest of these samples (Flom & Saudino, 2017a;Flom & Saudino, 2017b) used data from the parent-report Child Behavior Checklist (CBCL;Achenback & Rescorla, 2001) in N = 628 twins aged 2-3 years and estimated the heritability of CU traits at age 2 and 3 at 72% and 65%, respectively. Conversely, in a slightly older sample (age 5; Tuvblad, Fanti, Andershed, Colins, & Larsson, 2017), the teacher-report Child Problematic Traits Inventory (CPTI; Colins et al, 2014) in N = 1,189 twins generated the lowest reported estimate of heritability: 25%. The variation in heritability estimates for young children could be due to the different measures and reporters used, and these issues may be compounded by longitudinal non-invariance.…”
Section: Quantitative Genetic Studiesmentioning
confidence: 97%
“…These studies report a greater influence of genetic factors on CU traits in males as compared to females. However, others have failed to replicate these findings (Larsson et al, 2006;Ficks et al, 2014;Tuvblad et al, 2017), suggesting no consistent indication of quantitative sex effects. Only two studies have formally tested for qualitative sex effects (different sets of genes influencing CU in males vs. females), and neither found evidence for such differences (Larsson, Andershed, & Lichtenstein, 2006;Ficks, Dong, & Waldman, 2014).…”
Section: Quantitative Genetic Studiesmentioning
confidence: 99%
“…Tuvblad and colleagues’ study [ 70 ] on genetic and environmental determinants of the psychopathic personality in a community sample of 5-year-old twins indicated that both genetic and shared environmental influences are of importance for psychopathy personality traits in childhood. Regarding the CU dimension, they found a moderate (25%) genetic influence and a higher (48%) shared environmental influence.…”
Section: Factors Contributing To the Onset And Development Of Cu Traimentioning
confidence: 99%